2014
DOI: 10.1002/mrm.25561
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized [U-2H, U-13C]Glucose reports on glycolytic and pentose phosphate pathway activity in EL4 tumors and glycolytic activity in yeast cells

Abstract: A resonance at ∼181 ppm in the (13) C spectra of tumors injected with hyperpolarized [U-(2) H, U-(13) C]glucose was assigned to 6-phosphogluconate (6PG), as in previous studies in yeast, whereas in breast cancer cells in vitro this resonance was assigned to 3-phosphoglycerate (3PG). These peak assignments were investigated here using measurements of 6PG and 3PG (13) C-labeling using liquid chromatography tandem mass spectrometry (LC-MS/MS) METHODS: Tumor-bearing mice were injected with (13) C6 glucose and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 20 publications
1
39
1
Order By: Relevance
“…The oxidative branch generates NADPH and ribulose-5-phosphate in three irreversible reactions. The non-oxidative branch generates pentose phosphates for ribonucleotide synthesis in a series of reversible reactions that also recruit additional metabolites, such as fructose-6-phosphate (F6P) and glyceraldehyde-3-phosphate (G3P) (reviewed in REFS 11,12 ) (FIG. 2a).…”
Section: Reprogramming Of Glucose Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidative branch generates NADPH and ribulose-5-phosphate in three irreversible reactions. The non-oxidative branch generates pentose phosphates for ribonucleotide synthesis in a series of reversible reactions that also recruit additional metabolites, such as fructose-6-phosphate (F6P) and glyceraldehyde-3-phosphate (G3P) (reviewed in REFS 11,12 ) (FIG. 2a).…”
Section: Reprogramming Of Glucose Metabolismmentioning
confidence: 99%
“…2a), it has a pivotal role in cancer metabolism. The PPP is modulated by several metabolites, and in proliferating cancer cells both the oxidative and non-oxidative branches of the PPP are increased by several oncogenic drivers (reviewed in REFS 11,12 ). The extent to which the oxidative branch versus the non-oxidative branch is modulated depends on the redox and metabolic status of the cell.…”
Section: Reprogramming Of Glucose Metabolismmentioning
confidence: 99%
“…Previous reports have observed a chemical shift of [1- 13 C]-PEP ([ 13 C]-PEP) in a similar region as [ 13 C]-Pyr with a 1.7 ppm difference in the respective signals. 30 In our study at 3 T, spectral overlap of these metabolites cannot be discounted, which could result in potential contribution of [ 13 C]-PEP to the [ 13 C]-Pyr signal. Since the interconversion between pyruvate and lactate catalyzed by lactate dehydrogenase is generally in a fast chemical equilibrium, the lactate/pyruvate ratio has traditionally been employed in the evaluation of intracellular redox states.…”
Section: Resultsmentioning
confidence: 60%
“…However, 13 C carbonyl resonance assignments of metabolites based only on chemical shift and biochemical intuition could be problematic. Recently it was shown that a particular signal was assigned to 6-phosphogluconate (6PG) in tumors, but 3PGA in yeast and potentially in other systems [338]. The biochemical interpretation of these assignments is distinct, as 3PGA relates to glycolytic flux while 6PG reflects flux through the oxidative branch of the pentose phosphate pathway.…”
Section: Applications Of Nmr To Metabolomicsmentioning
confidence: 99%